Efficacy of platelet rich plasma (PRP) on mouth opening and pain after surgical extraction of mandibular third molars - Hanif Maidah; Sheikh Muhammad Azhar (EDP Sciences, 2021)
Introduction: Surgery of mandibular third molar teeth for removal is one of the most common procedures undertaken in oral and maxillofacial surgery departments. The complications created by the post extraction wound healing and physiological consecution of third molar surgery can affect patients' quality of life. Platelet rich plasma (PRP) is an autologous concentrate of platelets suspended in the Plasma that accelerates healing by concentration of growth factors which lessen the inflammation and as a result pain and trismus. Materials and methods: A Study was conducted on 130 patients at the department of Oral and Maxillofacial Surgery, FUCD Islamabad, for a period of 6 months after ethical approval. The patients with impacted mandibular wisdom teeth were selected and divided equally into two equal groups. The pain score was measured using the visual analogue scale (VAS) and trismus was measured using Vernier caliper before the surgery, immediately after surgery, on 3rd and 7th follow up visits. Results: The mean postoperative pain on 7th day was significantly lower in the PRP group with statistically significant P-value <0.0001. Trismus was also less reported in the PRP group with P-value <0.00065. Conclusion: Platelet Rich Plasma is effective to lessen trismus and pain after surgical removal of mandibular third molar teeth.